PERFORMANCE ANALYSIS AT THE SIGNALED INTERSECTION OF PATIH RUMBIH ROAD - JAVA ROAD - KERUING ROAD, KAPUAS REGENCY - Masardika, Eki; Widayanti, Nova (Universitas Lambung Mangkurat, 2026)
The intersection of Jalan Patih Rumbih-Jalan Jawa-Jalan Keruing is located in Kuala Kapuas and is part of the Trans Kalimantan Highway. The intersection experiences heavy traffic, especially in the morning and evening. To assess the performance of the intersection, the method used was direct observation. Furthermore, data analysis was carried out using the Indonesian Road Capacity Standard (PKJI 2023) guidelines. Based on the analysis and calculations, the densest traffic occurs between 4:00 PM and 5:00 PM. The results obtained for the current intersection condition are a Degree of Saturation of 0.788, an Intersection Delay of 39.15 seconds/smp, and a level of service D. Furthermore, alternative improvements were carried out so that the solution implemented to the problem was a geometric widening of the road to 10 meters for the main road and 9 meters for the secondary road with a change in signal to three phases. The average delay at the intersection is 22.27 seconds/smp, the degree of saturation reaches 0.392, and the cycle time is set at 74 seconds, with a service level index of C, which meets the criteria for a signalized intersection. Keywords: APILL, Urban Traffic Congestion, Degree of Saturation, Level of Service, Signal Cycle Optimization